Comparative study of Bupivacaine with magnesium sulfate versus bupivacaine with dexmedetomidine in peripheral nerve stimulator-guided transversus abdominis plane block for post-operative analgesia in cesarean section - Himanshu Sharma; Roopesh Kumar; Ashok Mittal; Mahesh Verma (Asian Journal of Medical Sciences, 2024)
Background: Magnesium sulfate and dexmedetomidine can be used as an adjuvant to local anesthetic solutions to enhance the quality and duration of peripheral nerve blocks. Aims and Objective: The objective was to compare magnesium sulfate and dexmedetomidine as adjuvants to bupivacaine (0.25%) in a transversus abdominis plane (TAP) block using a peripheral nerve stimulator (PNS) for post-operative pain relief in parturients undergoing caesarean delivery. Materials and Methods: A total of 150 pregnant women of ASA Grade I and II in the age range of 18–40, underwent elective cesarean delivery under the subarachnoid block, were divided into three groups of 50 each: Group A (bupivacaine and normal saline), Group B (bupivacaine and MgSO4), and Group C (bupivacaine and dexmedetomidine). Following caesarean delivery, all participants went through a bilateral PNS guided TAP block utilizing one of the treatment techniques. At 0 h, 2 h, 4 h, 6 h, 12 h, 24 h, and 48 h, all patients were monitored for pain, hemodynamic parameters, and side effects. Results: The present study was carried out on 60 patients of thyroid lesions, out of which 21 cases were benign and 39 cases were malignant lesions. Correlation between ICC and reverse transcription-polymerase chain reaction (RT-PCR), a significant correlation was observed between ICC and RT-PCR for BRAF mutation (P<0.001). As per location of tumor is concerned, no significant correlation was observed with BRAF through ICC (P>0.001). The total concordance between ICC and quantitative RT-PCR was 96.8% (Pearson Chi-square test P-value is less than the significance level (0.05), which was statistical significant (P<0.001). The sensitivity and specificity of BRAF ICC on cellblock in malignant thyroid lesions was 76.9% and 100%, respectively. The sensitivity and specificity of BRAF RT-PCR on cellblock in malignant thyroid lesions was 79.4% and 100%, respectively. The sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of combined BRAF ICC with RT-PCR was 96.8%, 100%, 100%, 90%, and 97.5%, respectively, on cellblock in malignant thyroid lesions. Conclusion: Dexmedetomidine and magnesium sulfate can be safely used as an adjuvant to bupivacaine (0.25%) to prolong the duration of pain relief while reducing the consumption of other analgesics without significant side effects.